Diferentes níveis de torta de nabo forrageiro (Raphanus sativus) como aditivo na silagem de capim elefante - Patiño Pardo, R.; Castello Branco Van Cleef, E. H. [UNESP]; Da Silva Filho, J. C.; Castro Neto, P.; Neiva, A. P. (My University, 2008)
The aim of the study was to evaluate the effects of the inclusion of different levels of turnip cake (TNF) on the chemical composition, digestibility and quality of elephant grass silage. Due to the quality of the oil extracted from the seeds, the turnip is being considered as an important option for the biodiesel industry in Brazil. The turnip cake is obtained from the mechanical pressing of the seeds to produce oil, and it differs from the meal by the content of fat. In the meal the fat is less than 1%, due to the use of solvents for the oil extraction. Experimental silos were used in a completely randomized design, in factorial arrangement 2 x 3 (two types of material and four levels of inclusion). The materials were represented for original material (fresh) and ensiled material, with four levels of inclusion of TNF (0, 3, 6, and 9%). Dry matter (DM), ether extract (EE), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), nitrogen indigestible neutral detergent (NIDN), nitrogen indigestible acid detergent (NIDA), ash (MM), lignin (LIG), buffer power (PT), calcium (Ca), phosphorus (P) and in vitro dry matter digestibility (IVDDM) were determined in all materials. In silage, additionally, were determined pH and amoniacal nitrogen (NH3-N). There were effects of inclusion of TNF and the type of material on the DM, CP, ADF, NIDA, P, and MM contents and on IVDDM. The interaction of the two factors was observed to the contents of CP, NDF, ADF, NIDA, Ca and IVDDM. In silage, the DM levels were lower (P < 0.05) than in original material. The values of DM were increased linearly as increased levels of inclusion of TNF. The fibrous components, including NIDN and NIDA, decreased linearly when the TNF increased. In all treatments, values of pH and N-NH3 considered ideal for good silage were observed. The IVDDM was reduced, linearly, with the addition of increasing levels of TNF. A negative correlation (-0.95) between IVDDM and content of EE may explain the tendency of this variable, due to the EE content increased linearly with the addition of TNF. The addition of TNF as an additive in silage of elephant diminished IVDDM. Considering the changes observed in the chemical composition and digestibility of elephant grass silage with TNF as additive, suggests that this should not be included at levels exceeding 3%. On the other hand, the silages with TNF as additive showed appropriate fermentation characteristics.
Different levels of turnip (Raphanus sativus) cake as additive in elephant grass silage
Keywords: Biofuel; Digestibility; Silage; Turnip; Brassica rapa subsp. rapa; Pennisetum purpureum; Raphanus sativus